2020
DOI: 10.7759/cureus.10858
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Degree of Acute Esophageal Injury Secondary to Corrosive Intake: Insights From a Public Sector Hospitals of a Developing Country

Abstract: Background Caustic ingestion continues to be a significant problem worldwide especially in developing countries and particularly in the age group of under six years. Ingestion of caustic substances is a medical emergency in both the adult and pediatric population and is associated with high morbidity and mortality. The ingestion of caustic substances induces an extensive spectrum of injuries to the aerodigestive tract, which includes extensive necrosis and perforation of the esophagus and stomach. Objectives T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…The female tendency for corrosive ingestion is well established and remains undisputed nationally and internationally 16,17 . A 2012 study in Macedonia reported ratio of females and males is 2.5:1.…”
Section: Discussionmentioning
confidence: 99%
“…The female tendency for corrosive ingestion is well established and remains undisputed nationally and internationally 16,17 . A 2012 study in Macedonia reported ratio of females and males is 2.5:1.…”
Section: Discussionmentioning
confidence: 99%
“…Post-corrosive esophageal stricture should highly consider inpatient with Zargar grade 2b and 3a [4,5,8,9,16,55]. Although various treatment strategies have been developed, none of them can provide outstanding results.…”
Section: Stricturementioning
confidence: 99%
“…As perfurações são oriundas de um grande grupo de etiologias, desde procedimentos terapêuticos por via endoscópica até ingestão de corpo estranho, substância corrosiva ou mesmo em decorrência de patologias específicas, tais como a síndrome de Boerhaave [4][5][6] . As fístulas, por sua vez, decorrem de uma gama de fatores, desde a evolução de uma deiscência, até complicações de doenças específicas, tais como a doença de Crohn 7 .…”
Section: Panoramaunclassified